EMPOWERMENT OF SCHOLARS: IMPROVING THE COMPETENCE OF WRITING SCIENTIFIC PAPERS OF STUDENTS AT UNIVERSITAS ISLAM NEGERI SULTAN SYARIF KASIM RIAU - Erdayani, Rizki; Afandi, Muslim; Afandi, Syed Agung (Dharma Pengabdian Perguruan Tinggi (DEPATI), 2024)
This activity aims to improve the ability of students of Universitas Islam Negeri Sultan Syarif Kasim Riau to publish scientific papers in reputable journals. This activity is the result of collaboration between the service team and the Research, Development, and Community Service Institute. The main problem that is the basis for this service activity is the low Sinta score of Universitas Islam Negeri Sultan Syarif Kasim Riau. This is caused by the low ability of students to publish scientific papers resulting from their collaboration with lecturers due to limited knowledge about reputable journals and standards for writing scientific articles in reputable journals. To overcome this problem, education was carried out on the use of the Sinta portal to obtain reputable journals that are relevant to the research topic, and education was also carried out on the standards for writing scientific articles in reputable journals. Based on the results of the evaluation carried out, there was an increase in participants' understanding of the use of Sinta as well as an increase in understanding of writing scientific articles in reputable journals. By increasing the two basic skills of publication in reputable journals, it is hoped that it can improve the quality of scientific papers of students at the Universitas Islam Negeri Sultan Syarif Kasim Riau, so that they can be published in reputable journals and have a positive impact on their Sinta scores.